Planejamento Espacial Marinho: mergulho em um oceano de conceitos - Raimundo Nonato Junior; Caio César Lima Dantas; José Luiz da Silva Neto (Confins)
The concept of marine spatial planning (MSP) is a recent development, developed over the last 20 years, driven by environmental policies of the UN and UNESCO in recent decades. This concept has been evolving in recent decades, revised based on the development of regional and national MSP policies that contextualize marine planning in different realities, in the face of attempts to reconcile sustainability and marine economy. This article reviews some international and national (Brazilian) documents that outline this concept over the last decades, analyzing the evolution of the concept, its power and its current challenges.